Identification and functional characterization of diterpene synthases for triptolide biosynthesis from Tripterygium wilfordii. (2nd December 2017) - Su, Ping; Guan, Hongyu; Zhao, Yujun; Tong, Yuru; Xu, Meimei; Zhang, Yifeng; Hu, Tianyuan; Yang, Jian; Cheng, Qiqing; Gao, Linhui; Liu, Yujia; Zhou, Jiawei; et al.
Summary: Tripterygium wilfordii, which has long been used as a medicinal plant, exhibits impressive and effective anti‐inflammatory, immunosuppressive and anti‐tumor activities. The main active ingredients are diterpenoids and triterpenoids, such as triptolide and celastrol, respectively. A major challenge to harnessing these natural products is that they are found in very low amounts in planta . Access has been further limited by the lack of knowledge regarding their underlying biosynthetic pathways, particularly for the abeo ‐abietane tri‐epoxide lactone triptolide. Here suspension cell cultures of T. wilfordii were found to produce triptolide in an inducible fashion, with feeding studies indicating that miltiradiene is the relevant abietane olefin precursor. Subsequently, transcriptome data were used to identify eight putative (di)terpene synthases that were then characterized for their potential involvement in triptolide biosynthesis. This included not only biochemical studies which revealed the expected presence of class II diterpene cyclases that produce the intermediate copalyl diphosphate (CPP), along with the more surprising finding of an atypical class I (di)terpene synthase that acts on CPP to produce the abietane olefin miltiradiene, but also their subcellular localization and, critically, genetic analysis. In particular, RNA interference targeting either both of the CPP synthases, TwTPS7v2 and TwTPS9v2, or the subsequently acting miltiradiene synthase, TwTPS27v2, led to decreased production of triptolide. Importantly, these results then both confirm that miltiradiene is the relevant precursor and the relevance of the identified diterpene synthases, enabling future studies of the biosynthesis of this important bioactive natural product. Significance Statement: Three functional (di)terpene synthases TwTPS7v2, TwTPS9v2 and TwTPS27v2 are shown to produce miltiradiene, which is a precursor to the antitumor triptolide in Tripterygium wilfordii .